2016
DOI: 10.1074/jbc.m116.723056
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-33 Regulates the Innate Immune Response via ATP Binding Cassette Transporter-mediated Remodeling of Membrane Microdomains

Abstract: MicroRNAs (miRNAs) 3 are small (ϳ22-nucleotide) noncoding RNAs that regulate gene expression by binding to partially complementary sites in the 3Ј-untranslated regions (UTRs) of specific mRNAs, thereby promoting degradation and/or repressing translation of target mRNAs. The human genome contains Ͼ2500 unique mature miRNAs (1). Because individual miRNAs typically have multiple targets, it is thought that Ͼ60% of all human genes may be subject to regulation by miRNAs (2). The promiscuity of miRNAs for target RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 59 publications
1
41
0
Order By: Relevance
“…Recently, miR-33 has also been implicated in the regulation of innate immunity by repressing the ATP-binding cassette A1 and G1 proteins in macrophages (89, 90). One of the main roles of the ABCA1/G1 proteins is to inhibit the assembly and activation of TLR4 (91).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, miR-33 has also been implicated in the regulation of innate immunity by repressing the ATP-binding cassette A1 and G1 proteins in macrophages (89, 90). One of the main roles of the ABCA1/G1 proteins is to inhibit the assembly and activation of TLR4 (91).…”
Section: Discussionmentioning
confidence: 99%
“…The previous study has demonstrated that ABCA1 expression can be negatively regulated by miR-33 [34,35]. Here, we examined whether miR-33 is involved in the augmentation of apigenin on ABCA1 expression and cholesterol efflux.…”
Section: The Stimulatory Effects Of Apigenin On Abca1 Expression and mentioning
confidence: 99%
“…In another recent study, Fessier and colleagues found that miR-33 regulates innate immune response via ABCA1 remodeling of membrane micro-domains. miR-33 augments macrophage lipid raft content and enhances pro-inflammatory cytokine induction and NFκB activation by LPS [47]. In contrast to Ouimet’s study, the authors found that LPS markedly reduces the expression of miR-33, which correlates with a significant downregulation of Srebp2 , the host gene for miR-33 [47].…”
Section: Introductionmentioning
confidence: 99%
“…miR-33 augments macrophage lipid raft content and enhances pro-inflammatory cytokine induction and NFκB activation by LPS [47]. In contrast to Ouimet’s study, the authors found that LPS markedly reduces the expression of miR-33, which correlates with a significant downregulation of Srebp2 , the host gene for miR-33 [47]. In agreement with this observation, numerous studies have shown that SREBP2 expression is significantly reduced in macrophages stimulated with LPS [48, 49].…”
Section: Introductionmentioning
confidence: 99%